The nitric oxide donating triamcinolone acetonide NCX 434 does not increase intraocular pressure and reduces endothelin-1 induced biochemical and functional changes in the rabbit eye. Issue 5 (18th January 2012) - Impagnatiello, Francesco; Giambene, Barbara; Lanzi, Cecilia; Pini, Alessandro; Somma, Teresa; Bastia, Elena; Ongini, Ennio; Galassi, Fernando; Masini, Emanuela
Abstract : Background: NCX 434 is a nitric oxide (NO)-donating triamcinolone acetonide (TA), shown to enhance optic nerve head (ONH) oxygen saturation in non-human primate eyes. Here, the effects of a single intravitreal (IVT) injection of TA were compared with those of NCX 434 on intraocular pressure (IOP), retinal function and retrobulbar haemodymamics in endothelin-1 (ET-1) induced ONH ischaemia/reperfusion in rabbits. Biochemical changes were also assessed in the aqueous humour and in retinal biopsies. Methods: IOP and resistivity index of ophthalmic artery (RI-OA) were recorded using TonoPen and ecocolor Doppler, respectively. Retinal function was assessed using photopic electroretinography. Cytokine expression and oxidative stress markers were evaluated with immunoassay techniques. Results: At 4 weeks post IVT treatment, TA increased IOP and RI-OA while NCX 434 did not (IOPVehicle =13.6±1.3, IOPNCX 434 =16.9±2.2, IOPTA =20.9±1.9 mm Hg; p<0.05 vs vehicle; RI-OAVehicle =0.44±0.03; RI-OANCX 434 =0.47±0.02; RI-OATA =0.60±0.04). Both NCX 434 and TA reversed ET-1 induced decrease in electroretinography amplitude to similar extents. NCX 434 attenuated ET-1 induced oxidative stress markers and nitrotyrosine in retinal tissue, and interleukin-6 and tumour necrosis factor-α in aqueous humour more effectively than TA. Conclusion: NCX 434 attenuates ET-1 induced ischaemia/reperfusion damage without increasing IOP, probably due to NO release. If data are confirmed in other species and models, this compound could represent an interesting new therapeutic option for retinal and ONH diseases, including diabetic retinopathy.